The effect of forced convection on coal combustion - Duranay, Neslihan; Pehlivan, Dursun (My University, 2002)
The objective of this study is to investigate the effect of the convection rate of air on the volatiles and char combustion rates of coal in a fixed bed system. Experiments were conducted to elucidate the effect of initial bed temperatures, type of coal and particle size and air flow rate through the vertical combustion chamber on the ignition and combustion times of Zonguldak coal, Cizre and Tunçbilek lignite. Experimental char combustion times of coals were compared to those found by computation using double resistance theory, and the active mechanism in the combustion of coal in fixed beds with a variety of air flow rates was supposed. It was found that convection rate of air had an effect on the ignition and volatiles combustion period of coals, but not on the char combustion periods. It was also concluded that both diffusion and chemical kinetics were important in the char combustion mechanism.
Zorlanmiş Konveksiyonun Bazi Kömürlerin Yanmasina Etkisi
Keywords: Coal; Combustion; Convection; Fixed bed